Flea Beetles of the Genus Altica: Altica spp. (Insecta: Coleoptera: Chrysomelidae) - Elenor F. Phillips; Jennifer Lynn Gillett-Kaufman (EDIS, 2019)
Flea beetles are in the largest subfamily (Alticinae) of the family Chrysomelidae, or leaf beetles (Furth 1988). The name Altica is derived from the Greek word haltikos, which translates to good jumper. Although this group of insects are named flea beetles, this is not because the form of the body resembles fleas, but rather because they have strong hind legs allowing them to jump long distances like true fleas (Siphonaptera). Their great jumping skills are thought to have evolved as a mechanism to escape from predators. This document is also available on the Featured Creatures website at http://entnemdept.ifas.ufl.edu/creatures/. https://edis.ifas.ufl.edu/in1238